Correlation between Abdominal Circumference and Serum High-Sensitivity C-Reactive Protein Concentration at Age 35–64 Years - Nabila Damayanti; Eveline Margo (Global Medical & Health Communication (GMHC), 2022)
The prevalence of central obesity in Indonesia is increasing every year. Based on data released by Riskesdas in 2018, there were 31% of the population aged 15 years and over suffer from central obesity, where the highest was found in the 45–54 years group (42.3%), followed by 44 years (39.2%) and 55–64 years group (39.1%). Central obesity can be measured by waist circumference or abdominal circumference, and it plays an important role in the occurrence of cardiovascular disease. Examining C-reactive protein (CRP) at low levels using high-sensitivity CRP (hs-CRP) methods will help to predict the risk of coronary heart disease. This study aimed to find the correlation between waist circumference and hs-CRP serum levels between the ages of 35 and 64. The study was an analytical observational with a cross-sectional approach attended by 25 respondents at Bhayangkara Hospital Tingkat I Raden Said Sukanto, Kramat Jati, East Jakarta, from October to November 2019. The waist circumference was measured with a metlin roll, and Prodia Laboratory took the blood to measure hs-CRP serum levels using ELISA methods. The data were analyzed using the Pearson correlation test. The results showed a correlation between waist circumference and hs-CRP serum levels with Sig. (2-tailed)=0.000 (p<0.05). There was a correlation between waist circumference and hs-CRP serum levels, which indicated that the greater the waist circumference, the higher levels of serum hsCRP would be.